Acute coronary syndromes in diabetes: Biomarkers of endothelial injury improve risk stratification and help identify predictors of risk. Issue 4 (April 2022) - Cordola Hsu, Amber R.; Fan, Wenjun; Harrington, Douglas; Wong, Nathan D.
Abstract: Background and aims: Patients with diabetes mellitus (DM) are at an increased risk of acute coronary syndrome (ACS); however, the factors predicting those at highest risk are not well understood. We identified risk factors in those with DM that best predict high ACS risk based on a multiple endothelial injury biomarker algorithm. Methods: We studied adults with DM from a clinical registry with measures of a coronary artery disease prediction algorithm (CADPA) score identifying 5-year ACS risk from nine markers. Stepwise logistic regression provided odds ratios for the relationship of age, gender, and individual risk factors not part of the CADPA algorithm with the likelihood of a high risk CADPA score. Results: We studied 1, 613 adults with DM (women: 47.3%, ages 22 to 100, mean age 63.2 years). Of these, 6.1% had a low, 13.2% intermediate, and 80.7% high risk CADPA score. From stepwise logistic regression, women were less likely to have a high risk CADPA score (odds ratio [OR] 0.21, 95% confidence intervals [CI] 0.15–0.29, p<.0001), while age (per standard deviation [SD]) (OR 5.04, [4.12–6.17], p<.0001), body mass index (BMI per SD) (OR 1.34, [1.14–1.58], p = 0.004), hypertension (OR 1.60, [1.15–2.24], p = 0.006), current smoking (OR 2.55, [1.56–4.16], p = 0.0002), hsCRP (per SD) (OR 1.24, [1.01–1.53], p = 0.04), and triglycerides (per SD) (OR 1.26, [1.04–1.54], p = 0.02) were more likely to have a high risk CADPA score. Conclusions: Age, men, hypertension, BMI, current smoking, hsCRP, and triglycerides are key factors in those with DM associated with higher ACS risk. Highlights: Over 70% of women and nearly 90% of men with diabetes are at high ACS risk based on a novel biomarker algorithm assessing endothelial damage. Age, hypertension, body mass index, smoking, hsCRP, and triglycerides are associated with higher ACS risk in diabetes. Among those with the high risk CADPA score, 94% women and 63% men missed by having a low or intermediate global risk estimate.